Regional energy- and mobility-aware routing protocol for hybrid wireless mesh network - Wenxiao Shi; Yuan Chai; Danni Liu (International Journal of Distributed Sensor Networks)
Existing routing protocols for hybrid wireless mesh network neglect the negative impact on network lifetime and route stability caused by energy constraints and mobility of mesh clients. To solve this issue, a regional energy- and mobility-aware routing protocol is proposed in this article. Both energy and mobility features in hybrid wireless mesh network are considered in this routing protocol. On one hand, within the communication transmission range, the intensity and degree of dispersion in energy consumption can be perceived. The node whose neighbor area has sufficient energy can be selected for network services, which can balance energy and extend the network lifetime. On the other hand, the mobility of clients is considered to enhance the stability and reduce network overhead. Therefore, regional energy- and mobility-aware routing protocol can balance network energy consumption, prolong network lifetime, and improve route stability. Simulation results via NS2 show that regional energy- and mobility-aware routing protocol can achieve better performance significantly.